Placenta Previa - Franco Gonzáles, Alberto (2015)
176 cases of placenta previa in the interval of ten years studied. The incidence does not vary during the course of the years. The most common variety was the central Total (31%) ended in cesarean Caesarean body having practiced by 57%. The delivery was spontaneous in 55 cases and was a cesarean hysterectomy. 34 cases were complicated by endometritis. Maternal deaths were due to uterine rupture and hypovolemic shock in one case and septic shock in a second case. The low perinatal mortality was due to handling these cases was established according to a pre scheme.